Insect Development, Thermal Plasticity and Fitness Implications in Changing, Seasonal Environments. (28th June 2017) - Buckley, Lauren B; Arakaki, Andrew J; Cannistra, Anthony F; Kharouba, Heather M; Kingsolver, Joel G
Synopsis: Historical data show that recent climate change has caused advances in seasonal timing (phenology) in many animals and plants, particularly in temperate and higher latitude regions. The population and fitness consequences of these phenological shifts for insects and other ectotherms have been heterogeneous: warming can increase development rates and the number of generations per year (increasing fitness), but can also lead to seasonal mismatches between animals and their resources and increase exposure to environmental variability (decreasing fitness). Insect populations exhibit local adaptation in their developmental responses to temperature, including lower developmental thresholds and the thermal requirements to complete development, but climate change can potentially disrupt seasonal timing of juvenile and adult stages and alter population fitness. We investigate these issues using a global dataset describing how insect developmental responds to temperature via two traits: lower temperature thresholds for development ( T 0 ) and the cumulative degree-days required to complete development ( G ). As suggested by previous analyses, T 0 decreases and G increases with increasing (absolute) latitude; however, these traits and the relationship between G and latitude varies significantly among taxonomic orders. The mean number of generations per year (a metric of fitness) increases with both decreasing T 0 and G, but the effects of these traits on fitness vary strongly with latitude, with stronger selection on both traits at higher (absolute) latitudes. We then use the traits to predict developmental timing and temperatures for multiple generations within seasons and across years (1970–2010). Seasonality drives developmental temperatures to peak mid-season and for generation lengths to decline across seasons, particularly in temperate regions. We predict that climate warming has advanced phenology and increased the number of generations, particularly at high latitudes. The magnitude of increases in developmental temperature varies little across latitude. Increases in the number of seasonal generations have been greatest for populations experiencing the greatest phenological advancements and warming. Shifts in developmental rate and timing due to climate change will have complex implications for selection and fitness in seasonal environments.